Kepekaan Enterobacteriaceae Asal Cobek Batu Gado-Gado Terhadap Amoxicillin, Chloramphenicol, dan Tetracycline - Hamida, Fathin; Ambarsari, Ratna; Djuhariah, Yayah Siti; Fahrudin, Fahri; Sholikha, Munawarohthus (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2024)
Enterobacteriaceae are non-spore-forming Gram-negative bacteria that are widespread throughout the world. Most members of the Enterobacteriaceae are pathogenic bacteria in humans, animals and plants. Treatment of infections caused by Enterobacteriaceae is to use antibiotics. Enterobacteriaceae resistance to antibiotics has been widely reported in previous studies. Infections caused by antibiotic-resistant bacteria are more difficult to treated and endanger health. This bacteria can enter the body, one of the ways is through contaminated food such as gado-gado. Gado-gado is a ready-to-eat food made from various raw or partially boiled vegetables mixed with peanut sauce. Making peanut sauce is made directly without cooking using a stone mortar. Gado-gado is often found being sold on the side of the road in unhealthy hygiene and sanitation conditions. One of the unhealthy sanitation factors is using a stone mortar repeatedly without washing it. This provides an opportunity for contamination of the stone mortar and gado-gado itself. This study tested the susceptibility of Enterobacteriaceae isolates to the antibiotics amoxicillin, chloramphenicol, and tetracycline isolated from gado-gado stone mortars. Antibiotic susceptibility testing used the Kirby-Bauer disc diffusion method. Based on the antibiotic susceptibility test, it was found that three isolates, namely isolates CB1B (Klebsiella pneumoniae), CB3B (Serratia fonticola), and CB4A (Salmonella enterica) were resistant to amoxcillin, two isolates, namely CB1A (Proteus mirabilis) and CB2A (Enterobacter sp.) were intermediate. to amoxicillin, and one isolate, namely CB2B (Enterobacter sp.), was sensitive to amoxicillin. All Enterobacteriaceae isolates were sensitive to chloramphenicol and tetracycline in this study.